‘Maintaining balance and harmony’: Javanese perceptions of health and cardiovascular disease - Fatwa S.T. Dewi; Lars Weinehall; Ann Öhman (Taylor & Francis Group, 2010)
Community intervention programmes to reduce cardiovascular disease (CVD) risk factors within urban communities in developing countries are rare. One possible explanation is the difficulty of designing an intervention that corresponds to the local context and culture. Objectives: To understand people's perceptions of health and CVD, and how people prevent CVD in an urban setting in Yogyakarta, Indonesia. Methods: A qualitative study was performed through focus group discussions and individual research interviews. Participants were selected purposively in terms of socio-economic status (SES), lay people, community leaders and government officers. Data were analysed by using content analysis. Results: Seven categories were identified: (1) heart disease is dangerous, (2) the cause of heart disease, (3) men have no time for health, (4) women are caretakers for health, (5) different information-seeking patterns, (6) the role of community leaders and (7) patterns of lay people's action. Each category consists of sub-categories according to the SES of participants. The main theme that emerged was one of balance and harmony, indicating the necessity of assuring a balance between ‘good’ and ‘bad’ habits. Conclusions: The basic concepts of balance and harmony, which differ between low and high SES groups, must be understood when tailoring community interventions to reduce CVD risk factors.